Charred Root of Meaning Rupture and Continuity in Christian Tradition - Rosemann, Philipp W. (2019)
Until very recently, the theological literature approached tradition almost exclusively as a phenomenon of continuity. But tradition involves several forms of rupture, both in its beginning and in its development. This paper distinguishes four: irruption (of the divine), forgetting, 'destruction' (together with retrieval/repetition), and exclusion. The argument draws on philosophers such as Martin Heidegger, Michel Foucault, and Jean-Luc Marion, but it is scripturally rooted and finds confirmation in Christian authors like Denys the Carthusian, Martin Luther, and Henri de Lubac.
Keywords: Mount Sinai; foolishness of the Cross; incident at Antioch; Mystical body; Tradition